miR-134 and miR-106b are circulating biomarkers for temporal lobe epilepsy: pilot study results - Kristina D. Lysova; Anna A. Usoltseva; Ekaterina A. Domoratskaya; Irina G. Areshkina; Natalia A. Shnayder; Diana V. Dmitrenko (Russian Open Medical Journal)
Temporal lobe epilepsy (TLE) is among the most common forms of focal epilepsy in adults. Currently, scientists search for microRNAs as noninvasive epilepsy biomarkers. MicroRNAs constitute a class of short (or small) non-coding RNAs that control the level of gene expression affecting the stability of mRNA. They are key regulators and therapeutic targets in epilepsy. Considering the role of miRNA-134 and miRNA-106b in the processes of epileptogenesis, the goal of our study was the clinical evaluation of their circulation as novel noninvasive molecular diagnostic markers of TLE. Material and Methods — Our pilot study involved 59 participants. The main group included 33 patients with mesial temporal lobe epilepsy, the control group encompassed 26 healthy volunteers. The ranking of patients was carried out depending on the disease duration, presence of epileptiform activity on the electroencephalogram (EEG) and hippocampal sclerosis on MRI, the number of taken antiepileptic drugs (AEDs), and patient response to the pharmacotherapy of epilepsy. The isolation of circulating microRNAs from blood plasma was accomplished via the sorption method, and the analysis of microRNA expression was performed by real-time PCR. Results — The expression levels of miR-134 and miR-106b in blood plasma in patients with TLE were reduced. Therefore, these microRNAs can be diagnostic biomarkers of patients with TLE, compared with the control group. The results of receiver operating characteristic (ROC) analysis yielded high sensitivity and specificity values of this biomarker for the diagnosis of TLE. Conclusion — Circulating miR-134 and miR-106b concentrations were significantly reduced in patients with mesial TLE (MTLE), compared with healthy controls. At the same time, the level of microRNA expression did not depend on the presence of hippocampal sclerosis and the response to antiepileptic therapy.